Sistem Informasi Geografis Berbasis Web Pada Industri Pariwisata - Pradigma Pradigma; Djumadi Sastro Wiyono (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2023)
Geographic Information System (GIS) is a type of software that can be used for input, storage, manipulation, display, and output of geographic information and its attributes (Prahasta). Geographic Information Systems have a very important role in combining data, organizing data, conducting data analysis which can ultimately produce data and can be used as a reference for decision making on issues related to geography.